The Decline and Rise of Neighbourhoods : the importance of neighbourhood governance - Somerville, Peter (2009)
There is a substantial literature on the explanation of neighbourhood change. Most of this literature concentrates on identifying factors and developments behind processes of decline. This paper reviews the literature, focusing on the identification of patterns of neighbourhood change, and argues that the concept of neighbourhood governance is a missing link in attempts to explain these patterns. Including neighbourhood governance in the explanations of neighbourhood change and decline will produce better explanatory models and, finally, a better view about what is actually steering neighbourhood change.